High-performance catalyst and method for recovering anhydrous sodium sulphate high-salt water by using high-performance catalyst
The multi-composite catalyst prepared by metal components such as magnesium salt, iron salt, lanthanum salt, cerium salt, etc. has solved the problems of existing catalysts not resistant to acid and low catalytic efficiency in wastewater treatment, and achieved efficient degradation of COD in wastewater, improving COD in wastewater The purity of Yuanming Powder products.
Patent Information
- Application Number
- CN202411813984.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing ozone catalytic oxidation catalysts cannot effectively reduce COD in wastewater, and a single metal oxide catalyst is not resistant to acid in actual wastewater treatment, metal elements are easy to dissolve, and catalytic efficiency is low.
Multivariate composite catalysts are prepared by metal components such as magnesium salt, iron salt, lanthanum salt, cerium salt, etc., and high-performance catalysts are prepared by impregnation method to improve catalytic activity and ozone utilization rate.
It significantly reduces COD in wastewater, improves the stability and activity of the catalyst, enhances the oxidation and degradation ability of organic matter, and improves the purity of Yuanming Powder products.
Smart Images

Figure 0XEFDGIK3C7HPNO1TYFDN2SSZMWCB14GK2NBMDWK 
Figure 4RJVNRAVJUKP2J8WTZW3EMT2DMXAZCFVRQTFOO3J
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment, and in particular relates to a high-performance catalyst and a method for recovering glauber salt high-salt water using the catalyst. Background Art
[0002] The presence of a large amount of salt and organic pollutants in high-salt wastewater will have a serious impact on the soil, water bodies, animals and plants in the ecosystem. For animals and plants, the salt in the wastewater will interfere with the internal osmotic pressure of the cells, inhibit the growth of animals and plants, affect the health of animals, and reduce the survival rate of plant seedlings. Continuous exposure to high-salt conditions will greatly reduce the abundance of species; for soil, the use of untreated saline wastewater for irrigation will cause the salt in the water to remain in the soil, leading to a series of problems such as land salinization and causing the loss of soil resources. Land salinization caused by the discharge of high-salt wastewater will also affect the growth of plants; for water bodies, the discharge of high-salt wastewater will have an adverse impact on the use of drinking water and other fresh water, leading to the salinization of freshwater resources. The presence of difficult-to-degrade organic pollutants in high-salt wastewater will also lead to water pollution, affect the growth of aquatic organisms, reduce the abundance of aquatic organisms, and thus destroy the ecological environment in the water. Therefore, the treatment of high-salt wastewater is very necessary.
[0003] Sodium sulfate (sodium sulfate) is the main component of high-salt wastewater in many industrial processes, such as white carbon black, chemical fiber, metallurgy, printing and dyeing industries, and its discharge volume is huge. When untreated sodium sulfate-rich wastewater is discharged into the environment, it will not only cause a huge waste of resources, but also cause a series of environmental pollution and water shortage problems, seriously restricting the sustainable development process of mankind. Therefore, the treatment technology of sodium sulfate-rich wastewater has received extensive attention from researchers at home and abroad, and the amount of research on the treatment of sulfate-rich wastewater continues to grow.
[0004] For the treatment of high-salinity wastewater, the commonly used methods can be divided into three methods: biological treatment, physical chemistry and advanced oxidation. In recent years, many advanced oxidation technologies have been gradually applied to wastewater treatment, such as ultraviolet-photocatalytic oxidation, electrochemical oxidation, wet chemical oxidation, heterogeneous ozone oxidation, etc. Among them, heterogeneous catalytic ozone oxidation technology has excellent characteristics such as high mineralization and no secondary pollution. However, problems such as catalyst stability and ozone utilization rate have become important constraints for the further promotion and application of this technology. Heterogeneous catalytic ozone oxidation technology is also called heterogeneous catalytic ozone oxidation technology. In recent years, it has important applications in the field of deep sewage treatment due to its advantages such as recyclable catalysts, no secondary pollution, high mineralization of organic pollutants in wastewater, and high ozone utilization rate. Adding heterogeneous catalysts on the basis of ozone oxidation can facilitate the decomposition of ozone and produce free radicals with stronger oxidizing ability, thereby triggering a redox chain reaction. The heterogeneous catalytic process can increase the degradation rate of organic matter. Therefore, it is of great practical and research significance to develop an ozone catalyst that is suitable for various conditions and wastewater from various processes, is easy to prepare, and is inexpensive, so as to improve the utilization rate and reaction rate of ozone and reduce the COD in the wastewater. Summary of the invention
[0005] In order to solve the technical problem in the prior art that ozone catalytic oxidation catalysts cannot effectively reduce the COD of wastewater, the present invention provides a high-performance catalyst and a method for recovering glauber salt high-salt water.
[0006] A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is (8-14): (6-8): (1.5-3): 1; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and allowing to stand to obtain a precursor solution; (3) After the precursor solution is dried, it is placed in a muffle furnace and calcined at 450-700°C to obtain a high-performance catalyst.
[0007] The use of carriers to prepare supported catalysts can greatly improve the catalytic activity of the catalyst. In the selection of catalysts, carrier materials that are easy to obtain, low in price, stable in nature, and highly corrosion-resistant are most suitable for industrial water treatment. On the one hand, they can reduce the cost and save costs. On the other hand, strong corrosion resistance can be applied to complex industrial water quality, and the stable nature can increase the number of times the catalyst is used, and prevent the dissolution of metal elements from causing secondary pollution of the water body. Supported catalysts mainly utilize the surface properties of the carrier to further improve the catalytic activity of the catalyst in catalytic ozone oxidation; this can increase the specific surface area of the catalyst and increase the active sites of the catalyst. Among them, the present invention uses γ-alumina as a catalyst carrier, because γ-alumina has the advantages of large specific surface area, high mechanical strength, and adjustable surface acidity and alkalinity.
[0008] In the actual wastewater treatment, heterogeneous ozone catalysts prepared from single metal oxides have problems such as acid resistance, easy dissolution of metal elements, and low catalytic efficiency. In order to solve this problem, the present invention prepares a multi-component composite catalyst by adding metal components such as magnesium salt, iron salt, lanthanum salt, and cerium salt based on the microstructure of the elements.
[0009] Among them, magnesium is an alkaline earth metal, and the loading of its oxide MgO can change the acid-base properties of the catalyst surface. And MgO can play a role in regulating pH in water. When the initial pH of the water is neutral or alkaline, MgO can effectively slow down the pH drop caused by small molecular organic acids produced by oxidation, thereby ensuring the efficiency of ozone catalysis to produce •OH. When the initial pH of the water is weakly acidic, MgO as a weakly alkaline substance can increase a certain pH. Based on this, the regulating effect of MgO on the pH of the water during the experiment is a key factor for MgO to play an ozone catalytic role. The variable valence state and rapid electron transfer characteristics of iron can realize the transformation of the valence state of iron ions and thus realize electron transfer during the ozone catalytic oxidation process, thereby improving the catalytic activity and ozone catalytic oxidation efficiency.
[0010] Although the active components of the catalysts used in this experiment are the same four metal oxides of magnesium, iron, lanthanum and cerium, the catalytic activities of the catalysts prepared under different active component ratios are significantly different. This is because the specific active component ratio will greatly enhance the synergistic effect between the active components, which will promote the decomposition of ozone to produce a large number of strong oxidizing substances such as hydroxyl radicals. Under a certain composition, MgO and iron oxides have a good synergistic catalytic effect. On the one hand, MgO will be dispersed around the iron oxide in a certain crystal form, improving the synergistic ability of iron oxides of different valence states in the process of mutual transformation, which is beneficial to the adsorption of ozone molecules by the catalyst in the catalytic ozone oxidation reaction; on the other hand, MgO and iron oxides will form specific active centers on the catalyst surface. These active centers can provide a large number of oxidative active sites, which will promote the decomposition of ozone, accelerate the transfer of electrons, and promote the continuous production of hydroxyl radicals by free radical chain reactions. The presence of a large number of hydroxyl radicals accelerates the oxidative degradation of organic matter and improves the removal rate of COD in water. On the other hand, the addition of lanthanum salt and cerium salt improves the dispersion of metal oxides on the surface of γ-alumina carrier, which can increase the specific surface area of the catalyst and greatly improve the catalytic activity. Among them, the amount of lanthanum salt with a smaller atomic radius should be more than that of cerium salt to better improve the dispersion of metal oxides. Furthermore, the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is (9-12): (6-8): (1.5-3): 1. By adjusting the ratio of each element, the catalytic efficiency can be better improved.
[0011] In order to improve the utilization rate of metal elements, the present invention loads the active components in the form of salt solution onto the surface and inside of the γ-alumina solid phase carrier material by impregnation. When the impregnation equilibrium is reached, the γ-alumina carrier is separated from the impregnation solution, and the loaded target elements are formed into a catalyst with catalytic activity through processes such as roasting and activation. The catalyst carrier prepared by the impregnation method can be directly obtained, and the step of catalyst molding is omitted, which greatly reduces the amount of active components and reduces the manufacturing cost. This aspect is particularly important for rare metal elements with good catalytic effects.
[0012] Furthermore, the ultrasonic power in step (1) is 200-400W.
[0013] Furthermore, in step (1), the magnesium salt, iron salt, lanthanum salt and cerium salt are respectively selected from magnesium nitrate (Mg(NO3)2), iron nitrate (Fe(NO3)3), lanthanum nitrate (La(NO3)3) and cerium nitrate (Ce(NO3)3).
[0014] Furthermore, in step (2), the average particle size of the γ-alumina carrier is 200-800 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt and cerium salt is (7-10):1.
[0015] Furthermore, in step (2), the stirring rate is 200-400 rpm; and the standing time is 8-12 h.
[0016] Furthermore, in step (3), the drying is carried out in an oven at 70-90° C. and the calcination time is 5-7 hours.
[0017] Furthermore, the calcination temperature is 500-600° C. If the calcination temperature is too low, the oxide crystal form may be imperfect; if the calcination temperature is too high, the support structure may collapse, which is not conducive to the increase of the surface area.
[0018] On the other hand, the present invention also provides a method for recovering sodium sulphate high-salt water by using a high-performance catalyst. The process for recovering sodium sulphate from sodium sulphate high-salt water comprises the following steps: firstly, the sodium sulphate high-salt water is sequentially filtered through a tubular membrane, acid adjustment and neutralization, a spiral membrane ultrafiltration, ozone catalytic oxidation, and a nanofiltration membrane separation process to obtain sodium sulphate nanofiltration concentrated water; then, the sodium sulphate nanofiltration concentrated water is evaporated and crystallized to obtain the product sodium sulphate; wherein, the ozone catalytic oxidation process is added with the high-performance catalyst for catalytic oxidation. The catalyst prepared by the present invention is used in the process for recovering sodium sulphate, which can fully reduce the COD in the wastewater and improve the purity of the sodium sulphate product.
[0019] Furthermore, in the ozone catalytic oxidation process, the dosage of the high-performance catalyst is 4-70 g / L, the ozone concentration is 30-70 ppm, and the pH is 8-14.
[0020] Beneficial effects: The present invention loads the active components in the form of salt solutions onto the surface and interior of the γ-alumina solid phase carrier material by impregnation, and the loaded target elements are formed into catalysts with catalytic activity through processes such as roasting and activation. The catalyst carrier prepared by the impregnation method can be obtained directly, eliminating the step of catalyst molding. Starting from the microstructure of the elements, the present invention prepares a multi-component composite catalyst by adding metal components such as magnesium salts, iron salts, lanthanum salts, and cerium salts. It solves the problems of heterogeneous ozone catalysts prepared from single metal oxides in actual wastewater treatment, such as acid resistance, easy dissolution of metal elements, and low catalytic efficiency. The catalyst prepared by the present invention is used in the recovery process of sodium sulphate, which can fully reduce the COD in the wastewater and improve the purity of the sodium sulphate product. DETAILED DESCRIPTION
[0021] The present invention will be explained in more detail below through specific embodiments. However, it should be understood that the specific functional details disclosed in this specification should not be interpreted as limiting, but only as the basis of the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.
[0022] Example 1 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 9:6:1.5:1; the ultrasonic power is 200 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 7:1; the stirring rate is 200 rpm; and the standing time is 8 h; (3) The precursor solution is dried and then calcined in a 500°C muffle furnace to obtain a high-performance catalyst; the precursor solution is dried in an oven at 70°C; the calcination time is 7 hours.
[0023] Example 2 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 12:8:3:1; the ultrasonic power is 400 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 10:1; the stirring rate is 400 rpm; and the standing time is 12 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 600°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 90°C; the calcination time is 5 hours.
[0024] Example 3 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 9:8:1.5:1; the ultrasonic power is 200 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 10:1; the stirring rate is 200 rpm; and the standing time is 10.5 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 600°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 90°C; the calcination time is 5.2 h.
[0025] Example 4 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 9.5:6.5:2:1; the ultrasonic power is 250 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3 wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 8:1; the stirring rate is 250 rpm; and the standing time is 9 hours; (3) The precursor solution is dried and then calcined in a muffle furnace at 520°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 75°C; the calcination time is 6.2 h.
[0026] Example 5 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 11:7.5:2.6:1; the ultrasonic power is 350 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 9:1; the stirring rate is 350 rpm; and the standing time is 11 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 580°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 85°C; the calcination time is 5.6 hours.
[0027] Example 6 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 10:7:2:1; the ultrasonic power is 300 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 8:1; the stirring rate is 300 rpm; and the standing time is 10 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 450°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 80°C; the calcination time is 6 hours.
[0028] Example 7 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 10:7:2:1; the ultrasonic power is 300 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 8:1; the stirring rate is 300 rpm; and the standing time is 10 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 700°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 80°C; the calcination time is 6 hours.
[0029] Example 8 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 8:7:2:1; the ultrasonic power is 300 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 8:1; the stirring rate is 300 rpm; and the standing time is 10 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 550°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 80°C; the calcination time is 6 hours.
[0030] Example 9 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 14:7:2:1; the ultrasonic power is 300 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 8:1; the stirring rate is 300 rpm; and the standing time is 10 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 550°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 80°C; the calcination time is 6 hours.
[0031] Example 10 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 10:7:2:1; the ultrasonic power is 300 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 8:1; the stirring rate is 300 rpm; and the standing time is 10 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 550°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 80°C; the calcination time is 6 hours.
[0032] Comparative Example 1 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 0:14:4:2; the ultrasonic power is 300 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of cerium nitrate in the impregnation solution is 0.3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 8:1; the stirring rate is 300 rpm; and the standing time is 10 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 550°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 80°C; the calcination time is 6 hours.
[0033] Comparative Example 2 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 15.4:0:3.1:1.5; the ultrasonic power is 300 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 8:1; the stirring rate is 300 rpm; and the standing time is 10 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 550°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 80°C; the calcination time is 6 hours.
[0034] Comparative Example 3 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 11.8:8.2:0:0; the ultrasonic power is 300 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 8:1; the stirring rate is 300 rpm; and the standing time is 10 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 550°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 80°C; the calcination time is 6 hours.
[0035] Comparative Example 4 A high performance catalyst, the preparation method of which comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is 10:7:1:2; the ultrasonic power is 300 W; the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively; the concentration of magnesium nitrate in the impregnation solution is 3wt%; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and standing to obtain a precursor solution; the average particle size of the γ-alumina carrier is 500 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt, and cerium salt is 8:1; the stirring rate is 300 rpm; and the standing time is 10 h; (3) The precursor solution is dried and then calcined in a muffle furnace at 550°C to obtain a high-performance catalyst; the precursor solution is dried in an oven at 80°C; the calcination time is 6 hours.
[0036] Performance Testing: BET analysis and catalytic performance analysis were performed on the high-performance catalysts prepared in Examples 1-10 and Comparative Examples 1-4. Using sodium sulfate high-salt wastewater as raw material, an ozone catalytic oxidation system was used to test the COD degradation rate in the wastewater with a reaction time of 75 minutes under the conditions of a high-performance catalyst dosage of 5 g / L, an ozone concentration of 40 ppm, and a solution pH of 10.
[0037] The sodium sulphate high-salt water was sequentially filtered through a tubular membrane, acidified and neutralized, a spiral membrane ultrafiltration, ozone catalytic oxidation, and a nanofiltration membrane separation process to obtain sodium sulphate nanofiltration concentrated water; then, the sodium sulphate nanofiltration concentrated water was evaporated and crystallized to obtain the product sodium sulphate, and the purity of the sodium sulphate was tested; wherein, the ozone catalytic oxidation process was respectively added with high-performance catalysts prepared in Examples 1-10 and Comparative Examples 1-4 for catalytic oxidation, the high-performance catalyst was added in an amount of 45 g / L, the ozone concentration was 60 ppm, and the solution pH was 10. The test results are shown in Table 1.
[0038] As can be seen from Table 1, the present invention loads the active components in the form of salt solution onto the surface and interior of the γ-alumina solid phase carrier material by impregnation, and the loaded target elements are formed into a catalyst with catalytic activity through processes such as roasting and activation. The catalyst carrier prepared by the impregnation method can be directly obtained, eliminating the step of catalyst molding. The present invention prepares a multi-component composite catalyst by adding metal components such as magnesium salts, iron salts, lanthanum salts, and cerium salts based on the microstructure of the elements. The problems of acid resistance, easy dissolution of metal elements, and low catalytic efficiency in the actual wastewater treatment of heterogeneous ozone catalysts prepared by single metal oxides are solved. The catalyst prepared by the present invention is used in the recovery process of glauber salt, which can fully reduce the COD in the wastewater and improve the purity of the glauber salt product. Specifically, it can be seen from Example 10 and Comparative Examples 1-3 that magnesium salts, iron salts and rare earth elements in a specific ratio can play a synergistic role. On the one hand, MgO will be dispersed around the iron oxide in a certain crystal form, improving the oxygen-cooperating ability of iron oxides of different valence states in the process of mutual conversion, which is beneficial to the adsorption of ozone molecules by the catalyst in the catalytic ozone oxidation reaction; on the other hand, MgO and iron oxide will form specific active centers on the catalyst surface, which can provide a large number of oxidation active sites, which will promote the decomposition of ozone, accelerate the transfer of electrons, and promote the continuous production of hydroxyl radicals by free radical chain reactions. The presence of a large number of hydroxyl radicals accelerates the oxidative degradation of organic matter and improves the removal rate of COD in water. On the other hand, the addition of lanthanum salts and cerium salts improves the dispersion of metal oxides on the surface of γ-alumina carriers, which can increase the specific surface area of the catalyst and greatly improve the catalytic activity. As can be seen from Comparative Example 4, the amount of lanthanum salts with smaller atomic radius should be more than that of cerium salts to better improve the dispersion of metal oxides.
[0039] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0040] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A high performance catalyst, characterized in that: The preparation method comprises the following steps: (1) dissolving magnesium salt, iron salt, lanthanum salt and cerium salt in water, and uniformly dispersing by ultrasonication to obtain an impregnation solution; the mass ratio of magnesium salt, iron salt, lanthanum salt and cerium salt is (8-14): (6-8): (1.5-3): 1; (2) placing the γ-alumina carrier in the impregnation solution, stirring evenly, and allowing to stand to obtain a precursor solution; (3) After the precursor solution is dried, it is placed in a muffle furnace and calcined at 450-700°C to obtain a high-performance catalyst.
2. The high performance catalyst according to claim 1, characterized in that The ultrasonic power in step (1) is 200-400W.
3. The high performance catalyst according to claim 1, characterized in that In step (1), the magnesium salt, iron salt, lanthanum salt and cerium salt are selected from magnesium nitrate, iron nitrate, lanthanum nitrate and cerium nitrate respectively.
4. The high performance catalyst according to claim 1, characterized in that In step (2), the average particle size of the γ-alumina carrier is 200-800 nm; the ratio of the mass of the γ-alumina carrier to the sum of the mass of the four salts of magnesium salt, iron salt, lanthanum salt and cerium salt is (7-10):
1.
5. The high performance catalyst according to claim 1, characterized in that In step (2), the stirring rate is 200-400 rpm; and the standing time is 8-12 h.
6. The high performance catalyst according to claim 1, characterized in that In step (3), the drying is carried out in an oven at 70-90° C.; the roasting time is 5-7 hours.
7. A method for recovering glauber salt high-salt water using the high-performance catalyst according to any one of claims 1 to 6, characterized in that: The following steps are involved: Firstly, the sodium sulphate high-salt water is sequentially filtered through tubular membrane, acid adjustment and neutralization, spiral membrane ultrafiltration, ozone catalytic oxidation and nanofiltration membrane separation processes to obtain sodium sulphate nanofiltration concentrated water; then, the sodium sulphate nanofiltration concentrated water is evaporated and crystallized to obtain the product sodium sulphate; wherein, the ozone catalytic oxidation process is added with the high-performance catalyst for catalytic oxidation.
8. The method for recovering glauber salt high-salt water using a high-performance catalyst as claimed in claim 7, characterized in that: In the ozone catalytic oxidation process, the dosage of the high-performance catalyst is 4-70 g / L, the ozone concentration is 30-70 ppm, and the pH is 8-14.
Citation Information
Patent Citations
Ozone catalytic oxidation catalyst for treating reverse osmosis concentrated water and preparation method of catalyst
CN105618080A
Ozone oxidation catalysis catalyst for degrading organic wastewater and preparing method thereof
CN110115999A
Preparation method for salt-tolerant catalyst for ozone catalytic oxidation for treating high-concentration brine in coal chemical industry
CN110743523A
Ozone advanced oxidation catalyst as well as preparation method and application thereof
CN118634837A
Printing and dyeing wastewater advanced treatment retrieval and utilization and zero discharging equipment
CN208234724U
Cited By
Catalyst for methane ultrahigh-temperature catalytic combustion as well as preparation method and application of catalyst
CN121797337A